Penerapan Model Pembelajaran Berbasis Proyek dengan Media Interaktif Educandy untuk Meningkatkan Hasil Belajar Siswa di SMP Negeri 7 Kuningan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of implementing a project-based learning model combined with the interactive media Educandy on students' learning outcomes. The research method used is a quantitative research method. The research design used is the One-Group Pretest-Posttest Design, which involves a pretest before treatment and a posttest after treatment. The subjects of the study are students from SMP Negeri 7 Kuningan. The population of this study consists of 1,115 students from SMPN 7 Kuningan, comprising 398 from grade VII, 382 from grade VIII, and 335 from grade IX, with the research sample taken from grade VII G, amounting to 40 students, consisting of 22 boys and 18 girls. The data collection techniques include observation, tests (pretest and posttest), interviews, and the methods of data analysis include descriptive tests, hypothesis testing (T-test), normality tests, validity tests, and reliability tests. The data processing for this research uses SPSS 26 for Windows. The results of this research conducted a hypothesis test with an average pretest score of 59.88 and a posttest score of 81.63. The t-test calculation yielded a significance value of 0.000, which is less than 0.05. This indicates a difference; therefore, H0 is rejected and H1 is accepted. It can be concluded that there is a significant improvement in the average learning outcomes of the students.